Preparation method of composite casting mold

By setting up dismantling sheets and vacuum degassing treatment on the graphite casting molds, and using ceramicization treatment of the water glass adhesive core, the problems of cumbersome dismantling of traditional graphite casting molds and easy damage to the mold shell core are solved, and the problem of Casting quality and production efficiency reduce costs.

CN119187450AActive Publication Date: 2024-12-27XIAN PUMP & VALVE GENERAL FACTORY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411276546.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-27
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

Traditional graphite castings are complicated and easy to be damaged during disassembly and recycling. The mold shell core is prone to deform or damage under extreme conditions, resulting in casting defects and waste of resources.

Method used

By adopting the composite casting method, the strength and high temperature resistance of the mold shell core are enhanced by setting a disassembly sheet on the graphite casting and vacuum degassing treatment, combined with the ceramicization of the water glass adhesive core.

Benefits of technology

The casting disassembly process is simplified, the production efficiency and casting quality are improved, the production cost is reduced, the casting defects caused by deformation or damage of the mold shell core are avoided, and the production needs of complex castings are adapted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119187450A_ABST
    Figure CN119187450A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite casting mold, and relates to the technical field of casting. Preparing a first graphite casting mold, and arranging a disassembly sheet on the back surface of a flange of the first graphite casting mold to obtain a second graphite casting mold; carrying out vacuum degassing treatment on the second graphite casting mold to obtain a third graphite casting mold; preparing a mold core mold; preparing sodium silicate binder type sand through a core mold; preparing a water glass binder composite core by hanging water glass binder type sand, and carrying out ceramization treatment on the water glass binder composite core to obtain a mold shell core; and the third graphite casting mold and the mold shell mold core are combined and assembled, and the composite casting mold is obtained. The water glass binder composite core is subjected to ceramic treatment, so that the strength and high temperature resistance of the mold shell core are enhanced, and the mold shell core can still keep stable shape under extreme casting conditions. The water glass is adopted to prepare the mold shell core, so that the preparation period is relatively short, the cost is lower, and powerful support is provided for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of casting technology, and in particular to a method for preparing a composite casting mold. Background Art

[0002] In the field of metal casting, graphite molds are widely used in the production of titanium, zirconium and their alloy castings due to their excellent thermal conductivity, high temperature stability and chemical inertness. However, with the continuous advancement of industrial technology and the increasing diversification of market demand, higher requirements are placed on the quality, production efficiency and cost control of castings.

[0003] Traditional graphite molds have many technical bottlenecks in disassembly and recycling, gas treatment, and mold shell and core preparation, which restrict the further development of the casting process. On the one hand, after the casting is completed, the traditional graphite mold is often difficult to disassemble quickly and effectively due to its complex structure and tight combination, which not only increases the labor intensity, but also prolongs the production cycle and increases the production cost. In addition, the mold is easily damaged during the disassembly process, further exacerbating the waste of resources. On the other hand, as a key component in the casting process, the performance of the mold shell and core directly affects the final quality of the casting. Traditional mold shell and core materials have deficiencies in strength, high temperature resistance and preparation cycle, and it is difficult to meet the production needs of complex castings. Especially under extreme casting conditions, the mold shell and core are prone to deformation or damage, resulting in defects in the casting and increasing the scrap rate. Summary of the invention

[0004] The embodiment of the present application solves the technical problems in the prior art that the graphite casting mold has a complex structure, a cumbersome and easily damaged disassembly process, and the mold shell and core are prone to deformation and damage by providing a composite casting mold preparation method.

[0005] An embodiment of the present application provides a method for preparing a composite mold, comprising: preparing a first graphite mold, and setting a demolding sheet on the back side of the flange of the first graphite mold to obtain a second graphite mold; vacuum degassing the second graphite mold to obtain a third graphite mold; preparing a core mold; preparing water glass binder molding sand through the core mold; preparing a water glass binder composite core by hanging sand with the water glass binder molding sand, and ceramicizing the water glass binder composite core to obtain a shell core; combining and assembling the third graphite mold with the shell core to obtain a composite mold.

[0006] In a possible implementation, a first graphite mold is prepared, and a mold removal sheet is set on the back of the flange of the first graphite mold to obtain a second graphite mold, including: a sand cleaning groove is set on the back of the mold removal sheet, and the depth of the sand cleaning groove is 1.5-10mm.

[0007] In a possible implementation, when the outer diameter of the dismantling sheet is not greater than 300 mm, the sand cleaning trough is a single-ring four-support structure; when the outer diameter of the dismantling sheet is greater than 300 mm, the sand cleaning trough is a double-ring eight-support structure.

[0008] In one possible implementation, the second graphite mold is subjected to vacuum degassing treatment to obtain a third graphite mold, including: placing the second graphite mold into a furnace, ensuring that the vacuum degree in the furnace reaches ≤100Pa, and then starting the heating process; gradually increasing the furnace temperature to 300-400°C, and keeping it within this temperature range for 4-6 hours; continuing to increase the furnace temperature to 900-1000°C, and keeping it within this temperature range for 4-6 hours; after the insulation is completed, allowing the furnace body to cool naturally to 400°C or below, and then taking out the second graphite mold to obtain a third graphite mold.

[0009] In a possible implementation, when the second graphite mold is loaded into the furnace, the larger and thicker parts of the second graphite mold are placed close to the heat source; and gaps should be left between the parts of the second graphite mold.

[0010] In a possible implementation, preparing a core mold includes: the core mold is a wooden mold, a metal mold, or a 3D printed plastic mold.

[0011] In a possible implementation, the material of the 3D printed plastic mold is PSB polystyrene powder or PLA polylactic acid or photosensitive resin, and the plastic filling rate thereof is 15-60%.

[0012] In a possible implementation, water glass binder molding sand is prepared by a core mold, including: using mullite molding sand and / or corundum sand as base materials, adding graphite powder or sawdust, stirring until the mixture is uniform, and obtaining mixed sand; when graphite powder is used, the weight of the graphite powder accounts for 5-25% of the total weight of the mixed sand; when sawdust is used, the weight of the sawdust accounts for 1-5% of the total weight of the mixed sand; after adding water glass to the mixed sand, stirring until the mixture is uniform, forming binder molding sand, wherein the weight ratio of water glass to mixed sand is 1-4:20; filling the binder molding sand into the core mold and compacting it, covering the mold cover, and then introducing carbon dioxide for hardening treatment; placing the hardened binder molding sand in a roasting furnace, drying it at a temperature of 100-300°C for at least 24 hours, and performing surface modification treatment to obtain water glass binder molding sand.

[0013] In one possible implementation, a water glass binder composite core is prepared by sand hanging with water glass binder sand, including: putting the water glass binder sand into a transition layer slurry barrel dedicated to titanium zirconium castings for slurry dipping, removing excess slurry after evenly spreading, placing it in a transition layer sand hanging equipment for sand pouring, and drying for at least 24 hours to obtain a transition layer core; putting the transition layer core into a slurry barrel dedicated to titanium zirconium castings for slurry dipping, removing excess slurry after evenly spreading, and placing it in a first surface layer sand hanging equipment for sand pouring, and drying for at least 24 hours to obtain a first surface layer core; putting the first surface layer core into a surface layer slurry barrel dedicated to titanium zirconium castings for slurry dipping, removing excess slurry after evenly spreading, and placing it in a second surface layer sand hanging equipment for sand pouring, and drying for at least 24 hours to obtain water glass binder sand.

[0014] In one possible implementation, a water glass binder composite core is ceramicized to obtain a shell core, including: loading water glass binder molding sand into a furnace, starting an air dust removal system, and then heating; gradually increasing the furnace temperature to 450°C and keeping it warm for 1-2 hours; continuing to increase the furnace temperature to 700°C and keeping it warm for 1-2 hours; then increasing the furnace temperature to 900-1150°C and keeping it warm for 1-2 hours; naturally cooling along with the furnace to a furnace outlet temperature not higher than 200°C to obtain a shell core.

[0015] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects:

[0016] The first graphite mold of the present application is provided with a disassembly sheet, which facilitates the disassembly and recycling process of the mold, effectively reduces the production cost and improves the production efficiency. The second graphite mold adopts a vacuum degassing treatment technology, which can deeply remove the gas and inclusions in the second graphite mold, thereby significantly improving the internal quality of the casting, greatly reducing the occurrence of common defects such as pores and shrinkage holes, and ensuring the high quality of the casting. In terms of the preparation of the shell core, the present application uses water glass as a raw material, and obtains a water glass binder composite core through careful blending and preparation. Furthermore, the present application ceramicizes the water glass binder composite core, which enhances the strength and high temperature resistance of the shell core, so that it can still maintain a stable shape under extreme casting conditions, and effectively avoids the problem of casting defects caused by deformation or damage of the shell core. In addition, the use of water glass to prepare the shell core not only has a relatively short preparation cycle, but also has a more economical cost, which provides strong support for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings required for use in the description of the embodiments of the present application. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0018] Figure 1 A flow chart of a method for preparing a composite casting mold provided in an embodiment of the present application;

[0019] Figure 2 A schematic diagram of the structure of a valve body casting prepared by a composite casting mold provided in an embodiment of the present application;

[0020] Figure 3 A schematic diagram of the structure of the core mold provided in the embodiment of the present application;

[0021] Figure 4 A schematic diagram of the structure of a disassembled sheet provided in an embodiment of the present application with an outer diameter of no more than 300 mm;

[0022] Figure 5 A schematic diagram of the structure of a disassembled sheet with an outer diameter greater than 300 mm provided in an embodiment of the present application;

[0023] Figure 6 A schematic diagram of the structure of the water glass binder molding sand provided in the embodiment of the present application;

[0024] Figure 7 A schematic diagram of vacuum degassing of a second graphite casting mold provided in an embodiment of the present application;

[0025] Figure 8 A schematic diagram of the structure of a pump body casting prepared by a composite casting mold provided in an embodiment of the present application.

[0026] Icon: 1-graphite upper mold; 2-disassembly sheet; 3-graphite middle mold; 4-graphite lower mold; 5-shell core; 6-core mold; 7-mold cover; 8-gate; 9-core bone. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0028] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship indicated by the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc. is based on the orientation or positional relationship shown in the drawings, and is only for the convenience of describing the embodiments of the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. The terms "first", "second", and "third" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance. In addition, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0029] The present application embodiment provides a method for preparing a composite casting mold, such as Figures 1 to 8 As shown, the preparation method of the composite casting mold comprises:

[0030] S1: Prepare a first graphite mold, and set a demolding sheet 2 on the back side of the flange of the first graphite mold to obtain a second graphite mold.

[0031] S2: vacuum degassing the second graphite casting mold to obtain a third graphite casting mold.

[0032] S3: Prepare a core mold 6.

[0033] S4: preparing water glass binder molding sand through the core mold 6.

[0034] S5: preparing a water glass binder composite core by sanding water glass binder molding sand, and ceramicizing the water glass binder composite core to obtain a mold shell core 5.

[0035] S6: Assemble the third graphite casting mold and the mold shell core 5 to obtain a composite casting mold.

[0036] Furthermore, the composite mold is placed in a vacuum solidification furnace for vacuum pouring to obtain a casting. The process of the embodiment of the present application reduces the chilling effect of the composite mold, so that the viscosity of the metal liquid during the pouring process is reduced, thereby increasing the fluidity of the metal liquid. This improvement effectively avoids the defects of the casting caused by premature cooling and solidification, and improves the flow and filling capacity of metal liquids such as titanium and zirconium. At the same time, the process also significantly reduces the probability of defects such as undercasting and lack of meat during casting molding, improves the surface finish of the core part of the casting, and further reduces the difficulty of cleaning the sand core of the casting.

[0037] Furthermore, the third graphite mold after casting is dismantled and recycled. Specifically, a dismantling sheet 2 is arranged on the back of the flange of the first graphite mold.

[0038] like Figure 2 As shown, the third graphite mold structure is a graphite lower mold 4, a graphite middle mold 3, a demolding sheet 2 and a graphite upper mold 1 from bottom to top, and each component is closely abutted. A pouring gate 8 is provided on the side of the graphite upper mold 1 away from the demolding sheet 2, and the pouring gate 8 is used for pouring. After the pouring is completed, the graphite upper mold 1 and the graphite lower mold 4 are first disassembled, and then the demolding sheet 2 is cleaned, and finally the graphite middle mold 3 is disassembled. Such a design makes the third graphite mold not only have a short manufacturing cycle, but also each part can be recycled and reused, effectively reducing the time cost of casting production, and significantly shortening the overall manufacturing cycle. In addition, the third graphite mold of the present application breaks through the size limitations of traditional molds, can flexibly adapt to the casting needs of large, medium and small titanium and zirconium castings, and provides an efficient and economical solution for production projects of different scales.

[0039] It should be noted that the first graphite mold of the present application is provided with a disassembly sheet 2, and the design of the disassembly sheet 2 facilitates the disassembly of the mold and the subsequent recycling process, effectively reduces the production cost, and improves the production efficiency. The second graphite mold adopts a vacuum degassing treatment technology, which can deeply remove the gas and inclusions in the second graphite mold, thereby improving the internal quality of the casting, greatly reducing the occurrence of common defects such as pores and shrinkage holes, and ensuring the high quality of the casting. In terms of the preparation of the shell core 5, the present application adopts water glass as a raw material, and obtains a water glass binder composite core through careful blending and preparation. Further, the present application ceramicizes the water glass binder composite core, enhances the strength and high temperature resistance of the shell core 5, and enables it to maintain a stable shape under extreme casting conditions, effectively avoiding the casting defect problem caused by deformation or damage of the shell core 5. In addition, the use of water glass to prepare the shell core 5 not only has a relatively short preparation cycle, but also has a more economical cost, which provides strong support for large-scale production.

[0040] In the embodiment of the present application, a first graphite mold is prepared, and a demolding sheet 2 is arranged on the back of the flange of the first graphite mold to obtain a second graphite mold, including:

[0041] S101: A sand cleaning groove is provided on the back of the demolding sheet 2, and the depth of the sand cleaning groove is 1.5-10 mm.

[0042] It should be noted that a sand cleaning trough is provided on the side where the demolding sheet 2 contacts the graphite medium 3 to provide sufficient space for the sand cleaning tool to operate, so as to facilitate disassembly. After the casting is poured, due to the shrinkage of the metal during solidification, the demolding sheet 2 may be subjected to a pre-tightening force due to the metal solidification shrinkage, which may cause the demolding sheet 2 to be tightly combined with the graphite medium 3, making it difficult to disassemble directly. However, the demolding sheet 2 and its supporting sand cleaning trough design in the present application effectively solve the disassembly problem. The present application uses a sand cleaning tool for careful cleaning, which can effectively remove the pre-tightening force generated by solidification shrinkage, thereby easily removing the remaining part of the medium-sized mold. This process not only reduces the deformation of the casting caused by isometric shrinkage, but also improves labor efficiency, reduces the difficulty of disassembling the third graphite mold, and improves the working environment and conditions of the graphite workers for demolding operations.

[0043] In the embodiment of the present application, the design of the disassembly sheet 2 takes into account the requirements under different outer diameters. Figure 4 and Figure 5 As shown, when the outer diameter of the demolding sheet 2 is not greater than 300 mm, a single-ring four-support structure of the sand cleaning trough is used; when the outer diameter is greater than 300 mm, a double-ring eight-support structure is used. Such a design helps to reduce casting deformation during the disassembly process and improve disassembly efficiency.

[0044] In the embodiment of the present application, the second graphite casting mold is subjected to vacuum degassing to obtain a third graphite casting mold, comprising:

[0045] S201: Load the second graphite casting mold into the furnace, ensure that the vacuum degree in the furnace reaches ≤100Pa, and then start the heating process;

[0046] S202: gradually increase the furnace temperature to 300-400°C and keep it within this temperature range for 4-6 hours;

[0047] S203: Continue to raise the furnace temperature to 900-1000°C and keep it within this temperature range for 4-6 hours;

[0048] S204: After the heat preservation is completed, the furnace body is allowed to cool naturally to 400° C. or below, and then the second graphite casting mold is taken out to obtain a third graphite casting mold.

[0049] It should be noted that during the entire vacuum degassing process of the present application, the supply of cooling water is continuous until the furnace temperature drops below 65° C. In addition, argon is strictly prohibited during the entire cooling process to avoid any factors that may affect the quality or safety of the casting.

[0050] Specifically, the treated third graphite mold should not be placed directly on the ground, in a humid or oily environment, and should be assembled and poured in time to ensure stable performance. If pouring is not performed temporarily, it should be stored in a drying oven (or insulation furnace) with the temperature controlled between 50-80°C. When taking out and placing the third graphite mold, the furnace door must be closed quickly to prevent changes in temperature and humidity from affecting the mold. The third graphite mold should be poured within five days after it is taken out of the furnace, otherwise it needs to be vacuum degassing again.

[0051] When taking the third graphite mold out of the drying box (heat-keeping furnace), be sure to quickly close the furnace door. It is strictly forbidden to keep the furnace door open for a long time to prevent the adverse effects of external temperature and humidity changes on the mold. Finally, the third graphite mold should be assembled and poured within five days after it is taken out of the furnace, otherwise it needs to be vacuum degassing again to ensure the quality of the casting.

[0052] In the embodiment of the present application, placing larger and thicker parts closer to the heat source can ensure that these parts can reach the required heating temperature faster. Since these parts are relatively large in volume and mass, they require more heat to heat evenly. Being closer to the heat source can shorten the heating time and improve the heating efficiency, thereby saving energy and shortening the production cycle.

[0053] In the embodiment of the present application, the core mold 6 is prepared, including: the core mold 6 is a wooden mold or a metal mold or a 3D printed plastic mold.

[0054] In the embodiment of the present application, the core mold 6 can be a wooden mold, a metal mold or a 3D printed plastic mold, wherein the material of the 3D printed plastic mold is PSB polystyrene powder, PLA polylactic acid or photosensitive resin, and the plastic filling rate is 15-60% to enhance the structural strength.

[0055] In the embodiment of the present application, the water glass binder molding sand is prepared by the core mold 6, including:

[0056] S401: Mullite molding sand and / or corundum sand are used as base materials, graphite powder or sawdust is added, and the mixture is stirred until uniformly mixed to obtain mixed sand.

[0057] It should be noted that the mullite sand or corundum sand has a mesh size of 60-100. The graphite powder has a mesh size of 60-300. The sand mixing of the present application can be processed manually or mechanically.

[0058] S402: When graphite powder is used, the weight of the graphite powder accounts for 5-25% of the total weight of the mixed sand; when sawdust is used, the weight of the sawdust accounts for 1-5% of the total weight of the mixed sand.

[0059] S403: After adding water glass to the mixed sand, stir until the mixture is uniformly mixed to form binder molding sand, wherein the weight ratio of water glass to the mixed sand is 1-4:20.

[0060] It should be noted that the stirring time is 5-10 minutes to ensure uniform mixing.

[0061] S404: Fill the core mold 6 with binder molding sand and compact it, cover the mold cover 7, and then introduce carbon dioxide to perform hardening treatment.

[0062] It should be noted that if Figure 8 As shown, the present application can place the binder molding sand in the core mold 6, and add the core bone 9 into the core mold 6. The adding method is: fill the core mold 6 with 30% to 60% of the sand, place the core bone 9, and then fill the remaining binder molding sand, and then proceed with the subsequent operation. The core bone 9 of the present application reduces the amount of sand filling, increases the strength of the binder molding sand, and avoids deformation and breakage of the binder molding sand during the later preparation, roasting and use process.

[0063] Specifically, the core bar 9 may be an iron wire steel rod with a diameter of 3 mm to 10 mm.

[0064] The curing time of the present application is 5-60 minutes. After the binder molding sand is fully hardened, the mold can be removed. The introduction of carbon dioxide can accelerate the hardening process of the binder molding sand, increase the hardening rate and hardening effect, and reduce pollution to the environment.

[0065] S405: placing the hardened binder molding sand in a roasting furnace, drying it at a temperature of 100-300° C. for at least 24 hours, and performing surface modification treatment to obtain water glass binder molding sand.

[0066] It should be noted that after drying, the surface is modified, including sanding with sandpaper to remove burrs and flash, and using titanium zirconium special graphite repair paste (neutral or alkaline) to repair pits. This series of treatments improves the accuracy and appearance quality of the binder molding sand. At the same time, the drying treatment also helps to further consolidate the structural strength of the binder molding sand and remove residual moisture.

[0067] In the embodiment of the present application, a water glass binder composite core is prepared by sanding water glass binder molding sand, including:

[0068] S501: Put the water glass binder molding sand into the transition layer slurry bucket specially used for titanium zirconium castings for slurry dipping, remove the excess slurry after evenly spreading it, and put it in the transition layer sand hanging equipment for sand spraying, dry it for at least 24 hours, and obtain the transition layer core.

[0069] It should be noted that the transition layer slurry specially used for titanium-zirconium castings should be kept neutral or alkaline.

[0070] First, place the water glass binder molding sand in a special transition layer slurry bucket for titanium zirconium castings for slurry treatment. After the slurry drips fully and ensures uniform coating, the subsequent sand hanging operation can be carried out.

[0071] This application is described by taking water glass slurry as an example.

[0072] The preparation method of the transition layer slurry for titanium zirconium castings is as follows: mix the high jade powder and / or mullite powder with water glass in a ratio of 4:1, and add appropriate amounts of surface wetting agent and defoaming agent. Specifically, the amount of surface wetting agent added should be controlled between 0.1-0.5% of the total amount of water glass, and the amount of defoaming agent added should be controlled between 0.01-0.25% of the total amount of water glass, so that the viscosity of the prepared slurry should be maintained in the range of 10-40 seconds (s).

[0073] If the slurry viscosity is too high, it can be adjusted by adding water glass in an appropriate amount; on the contrary, if the slurry viscosity is too low, it can be adjusted by adding an appropriate amount of powder. After the slurry is adjusted, it needs to be stirred for 1-2 hours to ensure that all components are fully mixed. After the performance parameters meet the standards, stop stirring and let the slurry recover for more than 4 hours, then turn on the stirring equipment again, and it can be used for the slurry treatment of molding sand.

[0074] After the slurry treatment of the water glass binder molding sand is completed, the slurry on the excess part is first scraped off with a scraper to ensure that the slurry is evenly distributed on the surface of the molding sand and not excessive. Then, the water glass binder molding sand is placed in a special transition layer sand hanging equipment. In the sand hanging equipment, the transition layer molding sand is evenly covered on the surface of the water glass binder molding sand that has been slurried by pouring sand. The transition layer molding sand can be zirconia molding sand, corundum molding sand or mullite molding sand. The transition layer molding sand should be controlled between 60-100 meshes to ensure the uniformity and density of the sand hanging layer.

[0075] After the transition layer is finished, the water glass binder molding sand needs to be placed in a specific drying environment for drying for at least 24 hours. The drying conditions should be strictly controlled within the range of 20-22°C and 55-65% humidity. At the same time, it is necessary to ensure that there is a visible breeze in the environment, but the wind speed should not exceed 2 meters per second. Such drying conditions help the moisture in the molding sand to evaporate evenly and slowly, avoiding problems such as cracks or deformation caused by too fast drying, thereby ensuring the quality of the transition layer.

[0076] S502: Place the transition layer core into a special slurry barrel for titanium zirconium castings for slurry dipping, remove the excess slurry after evenly spreading it, and place it in the first surface layer sand hanging equipment for sanding, dry it for at least 24 hours, and obtain the first surface layer core.

[0077] It should be noted that the special slurry for titanium zirconium castings involved in this application is the first surface layer slurry, and the first surface layer slurry remains neutral or alkaline to ensure good compatibility with the casting material. In the first surface layer slurry, the refractory aggregate is selected from high-purity yttria powder, high-purity zirconium oxide and various material powders (such as calcium yttrium, calcium zirconate, etc.) artificially synthesized for the refractory needs of titanium zirconium, and its particle size is strictly controlled at 325 meshes to ensure the fineness and uniformity of the first surface layer slurry. As the bonding core, the first surface layer slurry adopts a neutral or alkaline titanium zirconium special binder, such as a modified silica sol specially customized for titanium zirconium castings, to ensure a firm bond between the first surface layer slurry and the transition layer core.

[0078] In terms of the physical properties of the special slurry for titanium-zirconium castings, the viscosity needs to be maintained at 12±2S to ensure that the special slurry for titanium-zirconium castings is neither too thin nor too thick, and is easy to operate; the pH value of the special slurry for titanium-zirconium castings is 10-11 to further enhance its chemical stability; at the same time, the solid content is maintained at a high level of 80-85% to provide sufficient refractory and supporting properties; the slurry density is set in the range of 2.0-3.5g / ml to meet the specific requirements of the casting process.

[0079] A flexible and precise method is used to adjust the viscosity of the slurry for titanium-zirconium castings: if the viscosity is too high, a proper amount of binder or deionized water can be added for dilution; conversely, if the viscosity is too low, a proper amount of powder needs to be added to increase the viscosity. For the adjustment of the pH value, if the test finds that it is lower than the set range, a proper amount of tetraethylammonium hydroxide needs to be added to increase the pH value to ensure the stability and performance of the slurry.

[0080] After the titanium zirconium casting slurry is adjusted, it must be fully stirred for at least 4 hours to ensure that all components are evenly mixed and achieve the best performance. After all performance parameters are tested and meet the standards, the titanium zirconium casting slurry can be put into actual use and subsequent slurry bonding operations can be carried out.

[0081] The special slurry for titanium zirconium castings of this application is neutral or alkaline. The refractory aggregate is high-purity yttrium oxide powder, high-purity zirconium oxide or various types of artificially synthesized titanium zirconium refractory powders suitable for use (such as calcium yttrium, calcium zirconate, etc.), with a mesh size of 325 meshes, and the binder is a neutral or alkaline titanium zirconium special binder (such as modified silica sol for titanium zirconium castings). The slurry viscosity is 12±2S, the slurry pH value is 10-11, the solid content is 80-85%, and the slurry density is 2.0-3.5g / ml. The method for adjusting the viscosity here: if the viscosity is too high, you can add a binder or deionized water to adjust it. If the viscosity is too low, you can add powder to adjust it. If the pH value is too low, you need to add tetraethylammonium hydroxide to adjust it. The slurry adjustment must be stirred for more than 4 hours. After the performance parameters are tested and meet the standards, it can be used for slurrying.

[0082] Sanding the first surface layer: First, place the transition layer core in a special slurry barrel for titanium zirconium castings and evenly coat it with slurry. After the slurry drips fully and is evenly coated on the surface of the transition layer core, sand coating is performed. The molding sands used here include high-purity yttria molding sand, high-purity zirconium oxide molding sand, synthetic calcium zirconate molding sand, synthetic calcium yttrium molding sand, etc. The mesh number of the molding sand is controlled between 45-100 meshes. Sand coating can be performed by spraying sand, boiling bed or manual sand coating, among which the spraying sand coating method is recommended as the first choice due to its uniformity and efficiency.

[0083] First surface sanding and drying: After the first surface sanding operation is completed, the transition layer core must be dried immediately for at least 24 hours. The drying conditions should be strictly controlled within the range of 24-26℃ and 60-65% humidity, and ensure that there is no wind in the environment to avoid unnecessary cracks or deformation on the core surface.

[0084] S503: Place the first surface layer core into a special surface layer slurry barrel for titanium zirconium castings to dip in slurry, remove excess slurry after evenly applying it, and place it in the second surface layer sand hanging equipment for sanding, dry for at least 24 hours, and obtain water glass binder molding sand.

[0085] It should be noted that the special surface layer slurry for titanium zirconium castings in this application is the second surface layer slurry, and the second surface layer slurry needs to be neutral or alkaline. The refractory aggregate is high-purity yttria powder, high-purity zirconium oxide, or various types of artificially synthesized titanium zirconium refractory powders suitable for use (such as calcium yttrium, calcium zirconate, etc.), 325 mesh powder, and the binder is a neutral or alkaline titanium zirconium special binder (such as modified silica sol for titanium zirconium castings). Its configuration method is consistent with the first surface layer, with only some parameters being different, the slurry viscosity is 15±2S, the slurry pH value is 10-11, the solid content is 82-85%, and the slurry density is 2.5-3.5g / ml. The adjustment method of the second surface layer slurry is consistent with the first surface layer slurry.

[0086] Sanding the second surface layer: First, place the first surface layer core that has completed the first surface layer treatment in a special surface layer slurry barrel for titanium zirconium castings for the second slurry coating. After the second surface layer slurry is fully dripped and evenly coated on the surface of the core, sand coating is performed. The types of molding sand used this time are the same as those for the first surface layer, including high-purity yttria molding sand, high-purity zirconium oxide molding sand, synthetic calcium zirconate molding sand, synthetic calcium yttrium oxide molding sand, etc. The number of molding sand meshes is controlled between 45-100 meshes. Sand coating can also be done by sprinkling sand, boiling bed or manual sand coating, among which sprinkling sand is preferred due to its high efficiency and uniformity.

[0087] Second surface drying: The first surface core that has completed the second surface sanding operation needs to be dried for at least 24 hours. The drying conditions should be set within the range of 24-26℃ and 60-65% humidity, and ensure that there is no wind in the environment to prevent cracks or deformation on the core surface.

[0088] During or after the drying process, carefully check whether there are defects in the water glass binder sand, such as cracks, holes, etc. Any defects found must be repaired in time. When repairing, use the same slurry as the second surface layer and carefully apply it to the defects with a brush to ensure that the repair material is tightly combined with the surrounding sand. After the repair is completed, it is necessary to dry it again for at least 6-12 hours to ensure that the repaired part is fully cured.

[0089] In the embodiment of the present application, the water glass binder composite core is ceramicized to obtain the mold shell core 5, including:

[0090] S504: Load the water glass binder molding sand into the furnace, start the air dust removal system, and then heat it.

[0091] S505: gradually increase the furnace temperature to 450°C and keep it warm for 1-2 hours; continue to increase the furnace temperature to 700°C and keep it warm for 1-2 hours.

[0092] S506: After the furnace temperature is raised to 900-1150° C., the temperature is kept for 1-2 hours; the furnace is naturally cooled to a furnace outlet temperature not higher than 200° C., and a mold shell core 5 is obtained.

[0093] It should be noted that the surface of the water glass binder core to be fired should be intact and free of defects after the water glass binder sand is loaded into the furnace. First, turn on the air dust removal system, then turn on the power supply and fire according to the process system.

[0094] During the natural cooling process with the furnace, it must be ensured that the temperature when it is out of the furnace does not exceed 200°C. When the temperature in the furnace drops below 700°C, the furnace door can be opened appropriately to accelerate the cooling process, but this operation must be carried out with caution to avoid the adverse effects of drastic temperature changes on the mold shell core 5. At the same time, the control of the roasting temperature and time is crucial. If the roasting time is too long, the mold shell core 5 may burn out due to excessive heat, which will not only reduce its strength, but also may cause serious deformation problems. On the contrary, if the temperature is too low or the time is too short, the shell may not be fully sintered, thereby affecting its air permeability, and then leading to adverse conditions during the pouring process, such as gas retention, poor metal liquid penetration, etc. Therefore, in actual operation, the roasting temperature and time must be accurately set according to the specific material properties and process requirements, and the entire roasting process must be strictly monitored to ensure that the quality and performance of the mold shell core 5 meet the needs of subsequent processing and use.

[0095] The manufacturing process of the mold shell core 5 of the present application is significantly optimized, and only three layers of sand are needed to complete it. Compared with the prior art that requires several layers of sand to be hung in the core mold 6 and undergoes a complicated demoulding process, the present application not only simplifies the operation steps, but also greatly shortens the production cycle, effectively reducing the production cost. In addition, the present application reduces the product defect rate caused by improper operation by reducing the processing links, further improving product quality and production efficiency.

[0096] The prior art generally adopts the method of integrally calcining yttria or zirconium oxide core at high temperature, or adopts the layer-by-layer sand hanging technology to prepare the shell core 5 in the composite casting. However, both methods have the problems of long preparation cycle and high cost, especially for titanium or zirconium castings with high material cost, which further increases the manufacturing cost.

[0097] Furthermore, the graphite powder or sawdust introduced during the preparation of the shell mold core 5 will be gasified into carbon dioxide and discharged in the subsequent roasting stage, thereby forming a unique irregular hollow structure inside the shell mold core 5. This structure not only gives the shell mold core 5 excellent sintering strength, but also enables it to have excellent collapse performance. Therefore, in subsequent processing, the shell mold core 5 can adopt a variety of efficient cleaning methods such as water blasting sand cleaning or vibration sand cleaning to meet different production needs.

[0098] The method of the present application optimizes the production process of the mold shell core 5, shortens the production cycle and reduces the production cost. At the same time, the inner cavity smoothness and overall quality of the casting are improved through the unique sand cleaning tank design and ceramic treatment technology.

[0099] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other. Each embodiment focuses on the differences from other embodiments.

[0100] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A method for preparing a composite casting mold, characterized in that: include: A first graphite casting mold is prepared, and a mold removal sheet is arranged on the back of the flange of the first graphite casting mold to obtain a second graphite casting mold; The second graphite casting mold is subjected to vacuum degassing treatment to obtain a third graphite casting mold; preparing a core mold; preparing water glass binder molding sand by core mold; The water glass binder composite core is prepared by sanding the water glass binder molding sand, and the water glass binder composite core is ceramicized to obtain a mold shell core; The third graphite casting mold is assembled with the mold shell core to obtain a composite casting mold.

2. The method for preparing a composite casting mold according to claim 1, characterized in that: A first graphite mold is prepared, and a mold removal sheet is arranged on the back of a flange of the first graphite mold to obtain a second graphite mold, comprising: A sand cleaning groove is set on the back of the demolding sheet, and the depth of the sand cleaning groove is 1.5-10mm.

3. The method for preparing a composite casting mold according to claim 2, characterized in that: When the outer diameter of the dismantling sheet is not greater than 300mm, the sand cleaning tank is a single-ring four-support structure; When the outer diameter of the dismantled sheet is greater than 300mm, the sand cleaning trough is a double-ring eight-support structure.

4. The method for preparing a composite casting mold according to claim 1, characterized in that: The second graphite casting mold is subjected to vacuum degassing treatment to obtain a third graphite casting mold, comprising: Place the second graphite mold into the furnace, ensure that the vacuum degree in the furnace reaches ≤100Pa, and then start the heating process; Gradually increase the furnace temperature to 300-400℃ and keep it in this temperature range for 4-6h; Continue to raise the furnace temperature to 900-1000℃ and keep it in this temperature range for 4-6h; After the heat preservation is completed, the furnace body is allowed to cool naturally to 400°C or below, and then the second graphite mold is taken out to obtain a third graphite mold.

5. The method for preparing a composite casting mold according to claim 4, characterized in that: When the second graphite mold is loaded into the furnace, the larger and thicker parts of the second graphite mold are placed closer to the heat source; There should be gaps between the components of the second graphite mold.

6. The method for preparing a composite casting mold according to claim 1, characterized in that: Prepare a core mold, including: The core mold is a wooden mold, a metal mold or a 3D printed plastic mold.

7. The method for preparing a composite casting mold according to claim 6, characterized in that: The material of 3D printing plastic mold is PSB polystyrene powder or PLA polylactic acid or photosensitive resin, and its plastic filling rate is 15-60%.

8. The method for preparing a composite casting mold according to claim 1, characterized in that: The method for preparing water glass binder molding sand by a core mold comprises: Mullite molding sand and / or corundum sand are used as basic materials, graphite powder or sawdust is added, and the mixture is stirred until uniformly mixed to obtain mixed sand; When graphite powder is used, the weight of the graphite powder accounts for 5-25% of the total weight of the mixed sand; when sawdust is used, the weight of the sawdust accounts for 1-5% of the total weight of the mixed sand; After adding water glass to the mixed sand, stir until the mixture is uniform to form a binder molding sand, wherein the weight ratio of water glass to the mixed sand is 1-4:20; Fill the core mold with binder sand and compact it, cover the mold cover and introduce carbon dioxide to harden it; The hardened binder molding sand is placed in a roasting furnace, dried at a temperature of 100-300° C. for at least 24 hours, and subjected to surface modification treatment to obtain water glass binder molding sand.

9. The method for preparing a composite casting mold according to claim 8, characterized in that: The water glass binder composite core is prepared by sand hanging with water glass binder molding sand, including: Put the water glass binder molding sand into the transition layer slurry bucket for titanium zirconium castings for slurry dipping, remove the excess slurry after evenly spreading, and put it in the transition layer sand hanging equipment for sand spraying, dry for at least 24 hours, and obtain the transition layer core; Put the transition layer core into the special slurry barrel for titanium zirconium castings for slurry dipping, remove the excess slurry after evenly spreading, and put it into the first surface layer sand hanging equipment for sanding, dry for at least 24 hours, and obtain the first surface layer core; Put the first surface layer core into the special surface layer slurry barrel for titanium zirconium castings to dip in slurry, remove the excess slurry after evenly applying it, and put it in the second surface layer sand hanging equipment for sand spraying, dry for at least 24 hours to obtain water glass binder molding sand.

10. The method for preparing a composite casting mold according to claim 9, characterized in that: The water glass binder composite core is ceramicized to obtain a mold shell core, including: Put the water glass binder molding sand into the furnace, start the air dust removal system, and then heat it; Gradually increase the furnace temperature to 450°C and keep it at this temperature for 1-2 hours; Continue to raise the furnace temperature to 700℃ and keep it warm for 1-2h; Then raise the furnace temperature to 900-1150℃ and keep it warm for 1-2h; The mold shell core is obtained by naturally cooling with the furnace until the furnace exit temperature is not higher than 200°C.

Citation Information

Patent Citations

  • Precision casting method for graphite mould-ceramic core titanium alloy

    CN101733383A

  • Precision casting method for graphite mould-ceramic core titanium alloy

    CN104550755A

  • Casting technology of valve body

    CN110842146A

  • Cylinder type titanium alloy pouring mold capable of being repeatedly used and using method

    CN115889704A

  • Graphite-ceramic composite casting mold for casting titanium or titanium alloy, casting method and application

    CN118180326A